Hambur Balik Akustik Permukaan Substrat Dasar Perairan Menggunakan Echosounder Bim Tunggal - Baigo Hamuna; Lisiard Dimara; Sri Pujiyati; Nyoman Metta N. N. Natih (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2017)
The objectives of this research are to analyze the surface backscattering strength of seabed. The single beam echosounder Simrad EK15 with 200 kHz of frequencies was used for recordings of seabed acoustic backscattering. Data collection was conducted in April 29 – Mei 2 2017 which located in the Yos Sudarso Bay, Jayapura, Papua Province. Sampling substrate was taken for ground truth data using sediment grab. The results show that average value of surface backscattering strength of sand varied between -37.48 dB up -36.03 dB, and mud varied between -46.98 dB up -45.15 dB. It shows also that sand has a high substrate roughness, hardness, and grain size larger than the type of mud substrate. In acoustic backscattering values of sand were greater than mud.